A Comprehensive Approach to the Euro-Area Debt Crisis - Zsolt Darvas; Jean Pisani-Ferry; André Sapir (Hungarian Academy of Sciences, Institute of Economics, 2011)
The euro area's sovereign debt crisis continues though significant steps have been taken to resolve it. This paper proposes a comprehensive solution to the crisis based on three pillars: a plan to restore banking sector soundness in the whole euro area, a resolution of sovereign debt crisis -including a revision of EU assistance facilities and a reduction of the Greek public debt- and a strategy to foster growth and competitiveness. The paper provides novel estimates and analysis focusing on the current situation of Greece, Ireland, Portugal and Spain.
Keywords: F34; E60; H63; 330; fiscal sustainability; euro-area crisis; financial interdependence; Öffentliche Schulden; Staatsbankrott; Bankenregulierung; Haushaltskonsolidierung; Finanzpolitik; Wirtschaftspolitik; Griechenland; Irland; Portugal; Spanien